Scaling up nutrition through multisectoral planning: An exploratory review of 26 national nutrition plans. Issue 4 (8th June 2021) - Coile, Amanda; Wun, Jolene; Kothari, Monica T.; Hemminger, Carolyn; Fracassi, Patrizia; Di Dio, Debora
Abstract: With a growing consensus on the need to address malnutrition in a comprehensive and multisectoral way, there has been increased attention on the processes and factors for multisectoral nutrition planning to be successful. To guide countries, the Scaling Up Nutrition (SUN) Movement developed a checklist that defined characteristics of good national nutrition plans. This exploratory review used the framework of the Checklist to assess 26 national multisectoral nutrition plans (MSNPs) developed between 2014 and 2020. The MSNPs were assessed against a subset of 31 Checklist characteristics defined as basic plan components. Although the level of detail varied across the reviewed plans, the majority included core components that are important to facilitate effective planning and implementation, such as an assessment of the nutritional status and determinants of malnutrition for children under 5 years of age, a commitment to global recommendations related to reducing malnutrition, actions consistent with global evidence and responding to identified issues/gaps, governance arrangements to facilitate coordination, and identification of capacity‐building needs/actions to support effective implementation. Common gaps across plans included risk analysis and mitigation, defined responsible agencies for each action, an assessment of the financial gap and defined mechanisms for financial tracking and resource allocation, and mechanisms to coordinate operational research. These findings provide a high‐level, multi‐country review of multisectoral nutrition planning that can support future policymakers, technical assistance providers and regional and global stakeholders to consider the foundational elements of and further validate and address common shortcomings in developing such a plan.